Rare Sequence Variation Underlying Suspected Familial Cerebral Small‐Vessel Disease - Bernard P. H. Cho; Kate Auckland; Stefan Gräf; Hugh S. Markus (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Cerebral small‐vessel disease (cSVD) is the leading monogenic cause of stroke. Despite genetic screening in routine diagnosis, many cases remain without a known causative variant. Using a cohort with suspected familial cSVD and whole‐genome sequencing, we screened for variants in genes associated with monogenic cSVD and searched for novel variants associated with the disease. Methods and Results Rare variants were identified in whole‐genome sequencing data from the NBR (National Institute for Health Research BioResource Rare Disease) study. Pathogenic variants in known monogenic cSVD genes were identified. Gene‐based burden tests and family analysis were performed to identify novel variants associated with familial cSVD. A total of 257 suspected cSVD cases (mean ± SD age, 56.2 ± 16.1 years), and 13 086 controls with other nonstroke diseases (5874 [44.9%] men) were studied. A total of 8.9% of the cases carried a variant in known cSVD genes. Excluding these known causes, 23.6% of unrelated subjects with cSVD carried predicted deleterious variants in the Genomics England gene panel, but no association was found with cSVD in burden tests. We identified potential associations with cSVD in noncoding genes, including RP4‐568F9.3 (adjusted P = 7.1 × 10−25), RP3‐466I7.1 (adjusted P = 8.9 × 10−16), and ZNF209P (adjusted P = 1.0 × 10−15), and matrisomal genes (adjusted P = 5.1 × 10−6), including FAM20C, INHA, LAMC1, and VWA5B2. Conclusions Predicted deleterious variants in known cSVD genes were present in 23.6% of unrelated cases with cSVD, but none of the genes were associated with the disease. Rare variants in noncoding and matrisomal genes could potentially contribute to cSVD development. These genes could play a role in tissue development and brain endothelial cell function. However, further studies are needed to confirm their pathophysiological roles.